2021
DOI: 10.3390/su13063200
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of TiO2 NPs Effect as a Wastewater Treatment to Mitigate Cd Negative Impact on Bamboo Growth

Abstract: The recent emerging evidence reveals that titanium dioxide nanoparticles (TiO2 NPs) can be used as a wastewater treatment. This study provides new information about the possible detoxification role of TiO2 NPs as a wastewater treatment in plants under heavy metal stress, with an emphasis on the mechanisms involved. Here, we investigated the effects of TiO2 NPs as one wastewater treatment on a bamboo species (Arundinaria pygmaea L.) under in vitro Cadmium (Cd) toxicity conditions. A factorial experiment was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…The impact of TiO 2 NPs on increasing antioxidant activity and plant growth has been reported in several studies [13,14,46]. This increase can be attributed to the inductive role of TiO 2 NPs in enhancing signaling associated with the activation of antioxidant enzyme activity [13]. This finding is consistent with the reported results in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The impact of TiO 2 NPs on increasing antioxidant activity and plant growth has been reported in several studies [13,14,46]. This increase can be attributed to the inductive role of TiO 2 NPs in enhancing signaling associated with the activation of antioxidant enzyme activity [13]. This finding is consistent with the reported results in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Titanium, as a form of TiO 2 , has the ability to alter the bioavailability and behavior of metals in the environment [45]. The impact of TiO 2 NPs on increasing antioxidant activity and plant growth has been reported in several studies [13,14,46]. This increase can be attributed to the inductive role of TiO 2 NPs in enhancing signaling associated with the activation of antioxidant enzyme activity [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has high tolerance to grow in basic (alkaline), acidic, and neutral soils throughout the year ( Huang et al, 2020b ) and is cultivated in many areas and provinces in China such as Jiangsu province. On the other hand, HMs are one of the important toxic factors in water and soil in the Southwest regions of China ( Emamverdian et al, 2021a , b ), which pose significant risks to human health. An early survey conducted on edible plants in some local markets in China showed that the content of As was remarkably high in the shoots of bamboo species ( Zhao et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%